Are We Running Out of Truck Drivers? - Richard Beilock (EDIS)
Florida is almost totally dependent upon trucking for interstate shipments of its agricultural products, as well as for receiving many of the inputs for its industries and consumers. Since at least the early 1980s, there have been growing concerns over the ability of the U.S. labor force to supply drivers. If there is a persistent and growing shortfall in the supply of drivers, costs to Florida's industries (agricultural and non-agricultural) and consumers will rise. This is EDIS document, FE539, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published March 2005.